Maize Morphophysiological Changes Modulated by Cover Crops Rotation in Northeast Brazil - Souza, José Wilker Germano de; Luz, João Henrique Silva da; Silva, Dayane Mércia Ribeiro; Silva, Ricardo Barros; Costa, Bruno Richardson dos Santos; Melo, Alan Fontes; Santos, Hugo Rodrigues dos; Marques, Isabelly Cristina da Silva [UNESP]; Sousa, Jadielson Inácio de; Vanderley, Mariana Bernardino; Barbosa, Luana do Nascimento Silva; Farias, Maria Raquel da Silva; et al. (MDPI, 2024)
Cover crops have gained attention due to their potential benefits for the soil and physiological performance of subsequent crops. This study aimed to evaluate the physiological and productive aspects of maize grown in succession to cover crops in northeastern Brazil. A randomized complete block design with four repetitions was employed, in which the treatments consisted of the following cover crops: sunn hemp, spectabilis, pigeon pea, Brachiaria sp., jack bean, millet, and fallow. Physiological aspects and production components of maize were evaluated at the tasseling (VT) and smooth grain (R3) phenological stages. Millet cover increased carotenoid content in maize leaves by up to 78% at R3. Maize grown after pigeon pea, millet, and Brachiaria sp. showed up to 42% greater CO2 assimilation efficiency compared to jack bean. Carboxylation efficiency increased by up to 34% in maize grown after millet and Brachiaria sp., while water use efficiency improved by up to 76% in maize after sunn hemp and pigeon pea at R3. Sunn hemp, spectabilis, and jack bean reduced soil temperature by 2 °C compared to fallow. The highest maize yield was observed after jack bean, with an 8% increase over fallow. These findings demonstrate the benefits of incorporating cover crops into maize cultivation systems in the semi-arid region of Brazil.
Keywords: agricultural; Crotalaria juncea; Fabaceae; Poaceae; sustainability; yield; Zea maysL